Analisis Pengaruh Langsung dan Tidak Langsung Gaya Kepemimpinan terhadap Kinerja Dosen Universitas Katolik Widya Mandala Madiun dengan Budaya Organisasi sebagai Pemediasi - Antonius Dendy Al Tario (Fakultas Bisnis, 2017)
Employee performance is determined by many factors such as leadership style and organizational culture. This study aims to examine the direct and indirect effect of leadership style to the Universitas Katolik Widya Mandala Madiun lecturer’s performance trough organizational culture as mediating. The analysis method which been used is regression analysis and hypothesis testing. The result to our research can be concluded that leadership style has effect positively and significant to the organizational culture, leadership style has effect positively and significant to the lecturer’s performance, organizational culture has effect positively and significant to the lecturer’s performance, and leadership style indirectly influence to the lecturer’s performance through organizational culture as full mediation effect.